Proposed Marketing Strategy to Increase Sales Performance (Case Study: PT. Laku Emas Indonesia) - Prasetya, Indra (Eduvest - Journal of Universal Studies, 2023)
Laku Emas is a digital gold platform in Indonesia, where people can buy-sell-trade-pawn gold on the platforms. Upon its digitalization era, online investment is growing and massively popular. The problem however is that they are lacking customers and wish to increase the e-commerce sales. To analyze and research this both qualitative research methodology is used in this research to gain information and identify behavior, preferences and alternatives for improvement of actions. The primary data gathered is from interviewing potential customers of Lakuemas who know the brand and secondary through online reviews. For analysis technique, descriptive analysis is performed. Upon the research the main issue problems are identified based on customer experience journey and AARRR framework analysis. Lakuemas should further enhance their marketing strategy to be able to capture customers acquisition and retention.